Análise do crescimento intraurbano, vazios e áreas verdes: estudo de caso no município de São Carlos (SP) - Oliveira, Erica Zanardo (2017)
Among the effects of urban occupation and growth are the urban voids, which can be analyzed to assist in the study of urban dynamics. At the same time, many cities have a lack of green areas and their analysis also enables increase knowledge of local realities. In addition to the use of geoprocessing tools, the application of indexes such as urban green areas index and urban voids percentage, among others, can help further analysis and decision making for urban planning. In this sense, this research carried out analyzes of intra-urban growth, urban voids and green areas in the municipality of São Carlos – SP, covering the years 1998, 2004, 2010 and 2014. For this, it was used satellite images and Geographic Information Systems (GIS) software to quantify, categorize and evaluate intra-urban growth, local urban voids and green areas using index, multitemporal analyzes and comparisons with watersheds and local geological formations. The results showed that the urban voids reflected the dynamics of population growth, being occupied or created and varying their categories over time, reflecting in a decrease between the years studied. The green areas presented a growth, but with a lower index than the recommended by the UN and SBAU. The analysis of the urban voids and green areas allowed to identify sites with possible environmental fragility within the intra-urban area, such as the amount of urban voids in each geological formation and the existing uses within permanent preservation areas, which may induce improper occupation and use of these areas.